Exploring the Challenges and Opportunities in Management Accounting: A Study of ICMAB Journal Publications - Akhter, Farhana; Mustafa, Hasri; Wai, Lau Yeng; Abdullah, Amalina (Advances in Social Sciences Research Journal, 2025)
Due to the rapid expansion of management accounting both locally and globally, management accounting research has evolved in recent years. This paper paints a bleak image of the rewards and drawbacks associated with management accounting, especially in professional journals. Because management accounting challenges are widely recognized in professional publications, notably in ICMAB journals, the goals of this research are to investigate and assess these issues. According to our literature study, management accounting has accounted for just 7.93% of all articles published in the journal during the last ten years. Finance, corporate social responsibility, taxes, and financial reporting are among the remaining 92.07% of papers. Since, it is the primary journal for management accounting specialists in Bangladesh. ICMAB publications should cover more management accounting related content. Considering the limited number of management accounting papers published in ICMAB journals, the study makes several suggestions for efforts by journal editorial board members. It also extends an invitation to academics and professionals to conduct study on current challenges in management accounting.